Laser Synthesis of Hard Carbon for Anodes in Na‐Ion Battery. Issue 3 (19th December 2016) - Zhang, Biao; Deschamps, Michaël; Ammar, Mohamed‐Ramzi; Raymundo‐Piñero, Encarnacion; Hennet, Louis; Batuk, Dmitry; Tarascon, Jean‐Marie
Abstract : Advanced hard carbon is produced by short‐time laser irradiation, which increases the local ordered structure to give a high proportion of Na storage capacity in low voltage plateau. It could bring a 11% increase in energy density when matching with Na3 V2 (PO4 )2 F3 cathode to make a full cell.